Development of long-term primary cell culture of Macrobrachium rosenbergii: morphology, metabolic activity, and cell-cycle analysis - Sudarshan, Gurucharan; Weil, Simy; Manor, Rivka; Goldstein, Oron; Sultan, Eliya; Aflalo, Eliahu D.; Ofir, Rivka; Zimin, Sean V.; Rosental, Benyamin; Sagi, Amir (Frontiers in Marine Science, 2024)
This study describes our attempts to generate a sustainable cell culture of Macrobrachium rosenbergii. We present here a continuous longitudinal study on the embryonic primary cell culture of freshwater prawn M. rosenbergii that was uniquely monitored for up to 90 days with regard to its morphology, metabolic activity, and cell-cycle parameters. The daily monitoring of cells’ wellbeing and morphology showed seeded cells to be changing from attached singular diverse-sized cells after days 4–10 to interconnected clusters of cells, which apparently increased in number as detected by their density in the well. Moreover, the cultures demonstrated an autonomous transition during days 7–10, from completely two-dimensional (2D) morphology to a combination of 2D and three-dimensional (3D) growing structures, leading to the formation of multilayered spheroid-like cell masses. The metabolic activity of cultures showed a non-linear elevated pattern peaking on day 26, demonstrating proliferation and increment in the number of cells, retaining statistically significant elevated metabolic activity up to 40 days, and thereafter gradually declining. In parallel, cell-cycle analyses performed through florescence-activated cell sorting (FACS) showed that the G0/G1 and S phases were inversely proportional to each other. Proliferation, based on metabolic activity, in the cultures was sustained by a significant increase in the portion of cells arrested in the S phase, from day 4 up to day 24, and then a decrease between days 45 and 90. Sorting the populations in the M. rosenbergii primary embryonic cell culture on days 3 and 24 revealed eight seeded populations, most of them expressing the putative proliferation markers MrMYC and MrPCNA, while six of them expressed also the putative stem-cell markers MrOct-4 and MrSox-2/3. Therefore, assuming the increment in cell density and metabolic activity and the reduction in G0/G1 distribution toward S, as well as the increment in G2/M, all pointing toward proliferation, we further hypothesized that splitting the cultures along the experiment at the high-proliferating mitotic ratio peaks would enable successful passages. Indeed, in prawn embryonic primary cell culture, we succeeded in executing two consecutive passages: the first after 8 days in culture and the second 4 days following the first passage. Cells after both passages expressed the species-specific Mr18S, along with the proliferative markers MrMYC and MrPCNA and the stem-cell markers MrOct-4 and MrSox-2/3. After several decades of research efforts to establish a crustacean cell line—with no published success—here, we present M. rosenbergii cultures composed of putative proliferating/stem-cell subpopulations or appearing like clones. These mix-population prawn embryonic primary cell cultures could serve as a basic platform for immortalization and contribute to the long-term goal of establishing sustainable cell-culture lines.